2018
DOI: 10.21608/ijhth.2019.32001
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Affecting Guests’ Consumption Behaviors toward Open Buffets to Avoid Food Leftovers in Sharm El Sheikh Hotels

Abstract: One of the biggest contemporary challenges of management in the food service sector is the highest consumer food leftovers which points to room for improvements in this area. Buffet leftovers are also a serious concern for hotels in the developing countries due to several negative consequences on the environment and food resources and security. Therefore, it is a focal point of interest in media, politics, research, and business. Guest behavior is claimed to be the main cause of food leftovers at the consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
(67 reference statements)
1
1
0
Order By: Relevance
“…This implies that cultural beliefs significantly influence the food consumption behavior of diners in restaurants in 4-5 star hotels in Nairobi County. The results are consistent with the findings of Qoura and Ali (2018), which demonstrated that beliefs have an impact on food consumption in situations where some meals are forbidden, requiring specific techniques of preparation, or during periods of fasting or feasting. The guests hold divergent opinions regarding their dietary preferences when dining at eateries.…”
Section: Table 3: Influence Of Cultural Beliefs On Food Consumption B...supporting
confidence: 90%
See 1 more Smart Citation
“…This implies that cultural beliefs significantly influence the food consumption behavior of diners in restaurants in 4-5 star hotels in Nairobi County. The results are consistent with the findings of Qoura and Ali (2018), which demonstrated that beliefs have an impact on food consumption in situations where some meals are forbidden, requiring specific techniques of preparation, or during periods of fasting or feasting. The guests hold divergent opinions regarding their dietary preferences when dining at eateries.…”
Section: Table 3: Influence Of Cultural Beliefs On Food Consumption B...supporting
confidence: 90%
“…According to Gurbuz and Macabangin (2019), in a study on factors affecting consumers' behavior in purchasing products, it is pointed out that cultural aspects and consumption have a substantial connection. Similarly, Qoura and Ali (2018) also noted that culture is a significant determinant influencing food consumption; the cultural background of individuals impacts their attitudes and behaviours towards products and their food consumption habits, ultimately influencing their purchasing decisions and actions related to buying goods and services (González et al, 2019). Within a specific group, culture influences what food is acceptable or unacceptable, affecting the type of ingredients used and considered suitable.…”
Section: Understanding the Role Of Cultural Practices On Food Consump...mentioning
confidence: 99%